2015
DOI: 10.1002/2015jd023762
|View full text |Cite
|
Sign up to set email alerts
|

Black carbon concentrations in snow at Tronsen Meadow in Central Washington from 2012 to 2013: Temporal and spatial variations and the role of local forest fire activity

Abstract: Characterizing black carbon (BC) concentrations in the seasonal snowpack is of interest because BC deposition on snow can reduce albedo and accelerate melt. In Washington State, USA snowmelt from the seasonal snowpack provides an important source of water resources, but minimal work has been done characterizing BC concentrations in snow in this region. BC concentrations in snow were monitored over two winters (2012 and 2013) at Tronsen Meadow, located near Blewett Pass in the eastern Cascade Mountains in Centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 48 publications
1
21
0
1
Order By: Relevance
“…Observations of BC in melting snow support the accumulation of BC near the surface (Xu et al, 2012;Doherty et al, 2013;Sterle et al, 2013;Delaney et al, 2015). In a sequence of snow pits, Sterle et al (2013) showed that during the ablation season, BC mixing ratios increase significantly near the snow surface (sampled in the top 2 cm) relative to bulk BC concentrations.…”
Section: Parameter Sensitivitymentioning
confidence: 95%
See 1 more Smart Citation
“…Observations of BC in melting snow support the accumulation of BC near the surface (Xu et al, 2012;Doherty et al, 2013;Sterle et al, 2013;Delaney et al, 2015). In a sequence of snow pits, Sterle et al (2013) showed that during the ablation season, BC mixing ratios increase significantly near the snow surface (sampled in the top 2 cm) relative to bulk BC concentrations.…”
Section: Parameter Sensitivitymentioning
confidence: 95%
“…They suggest that most likely a large fraction of previously deposited BC becomes concentrated near the surface. Delaney et al (2015) also report surface BC increase during melt, to which BC being trapped at the snow surface is likely to contribute. BC increases in surface snow of up to an order of magnitude (Sterle et al, 2013;Doherty et al, 2016) and more (Xu et al, 2012) have been observed in natural snow during melt.…”
Section: Parameter Sensitivitymentioning
confidence: 99%
“…1) on Holtedahlfonna. Forsström et al, 2013;Delaney et al, 2015). Consequently, the similarity in EC concentrations measured at stake 10 (2015 coring site) from the surface snow, snow pack and firn core samples gives confidence on the reproducibility of the used EC analysis method.…”
Section: Post-depositional Processes Affecting Ec Deposition At the Tmentioning
confidence: 99%
“…Their extensive measurements of snow albedo and snow properties detailed in these three papers culminate with the development of a physically based snow albedo model, which is comparable to the SNICAR model developed by Flanner et al [2007]. In the western U.S., a number of studies have been conducted on the influence of impurities on snow albedo [Doherty et al, 2014[Doherty et al, , 2016Kaspari et al, 2014Kaspari et al, , 2015Delaney et al, 2015;Painter et al, 2007bPainter et al, , 2012Skiles et al, 2012Skiles et al, , 2015. collected a similar data set to ours, with daily field measurements of albedo and snow properties in the Rocky Mountains in the western U.S..…”
Section: Introductionmentioning
confidence: 99%
“…There is a general understanding of the physics that control the albedo of snow, but different factors dominate changes in albedo at various locations. The presence of impurities, particularly dust and black carbon, in snow is one factor that has received much attention in recent scientific research [e.g., Ramanathan and Carmichael, 2008;Flanner et al, 2007;Hansen and Nazarenko, 2004;Sterle et al, 2013;Doherty et al, 2014Doherty et al, , 2016Kaspari et al, 2014Kaspari et al, , 2015Delaney et al, 2015;Painter et al, 2007bPainter et al, , 2012Skiles et al, 2015;Polashenski et al, 2015;Dang et al, 2015;Oaida et al, 2015;Yasunari et al, 2015;Qian et al, 2015]. Using our extensive measurements in New Hampshire, we assess the reduction of snow albedo due to impurities in comparison to other factors.…”
Section: Introductionmentioning
confidence: 99%